2011
DOI: 10.1002/ceat.201000462
|View full text |Cite
|
Sign up to set email alerts
|

Micronization of Fluticasone Propionate using Supercritical Antisolvent (SAS) Process

Abstract: The micronization of an asthma active pharmaceutical ingredient, fluticasone propionate, using the supercritical antisolvent (SAS) process was investigated in this study. The most commonly used supercritical carbon dioxide was employed as the antisolvent. The effects of five process parameters, including operating temperature, operating pressure, solution flow rate, solution concentration, and nozzle diameter, were compared and discussed. The physical properties of micronized fluticasone propionate were examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 43 publications
1
8
0
Order By: Relevance
“…27 Previous researchers have also reported similar results. 28,29 effect of concentration of solution As indicated in Figures 4 and 5, the concentration of solution had a slight effect on particle size; hence, the higher the concentration of solution, the smaller the particle size. Runs 6 and 14 (Table 2) showed that an increase in the concentration of curcumin solution from 0.5% to 1% can decrease the size of curcumin nanoparticles from 386 to 334 nm.…”
mentioning
confidence: 92%
“…27 Previous researchers have also reported similar results. 28,29 effect of concentration of solution As indicated in Figures 4 and 5, the concentration of solution had a slight effect on particle size; hence, the higher the concentration of solution, the smaller the particle size. Runs 6 and 14 (Table 2) showed that an increase in the concentration of curcumin solution from 0.5% to 1% can decrease the size of curcumin nanoparticles from 386 to 334 nm.…”
mentioning
confidence: 92%
“…SAS particles can be used for oral, parenteral, and topical drug administration; in the latter case, the micronized drug particles can be incorporated into various types of dressings or supports. Up to now, SAS-micronized drugs were proposed for different diseases or clinical conditions, including inflammations and pains [11,12,75,84], infections [2,4,25,58,59,61,63,64,74,77,85,86], diabetes [5,7,66], psychological disorders [87], asthma [32,71,88], tumors [1,3,4,31,38,[67][68][69]78,[89][90][91][92], cardiovascular pathologies [6,33,70,76], etc.…”
Section: Sas Micronization Of Active Compoundsmentioning
confidence: 99%
“…One of the widely used crystallization processes is solventantisolvent crystallization (SAC), which reduces the size [13,14] and changes the morphology of high-energy materials [15][16][17][18]. In SAC, the solute and antisolvent can be dissolved in the solvent, but the solute is insoluble in the antisolvent.…”
Section: Introductionmentioning
confidence: 99%